Multi-layer hybrid coating with biomimetic cell membrane structure and preparation method of multi-layer hybrid coating

By forming a multi-layer hybrid coating on the surface of magnesium metal, combined with microarc fluorination and nano-hydroxyapatite-induced bionic mineralization technology, the problem of excessive corrosion rate after magnesium metal implantation is solved, and the high performance and good biocompatibility of magnesium-based implantation devices are achieved.

CN119564931AActive Publication Date: 2025-03-07STOMATOLOGICAL HOSPITAL TIANJIN MEDICAL UNIV +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202510140143.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The corrosion rate of magnesium metal after implantation into the human body is too fast and uncontrollable, resulting in poor histocompatibility, poor bone tissue repair effect, and safety hazards of tissue necrosis, limiting its clinical application.

Method used

A multi-layer hybrid coating with a biomimetic cell membrane structure, including a porous coral-like MgF2 transition layer formed on the magnesium-based metal surface and an alternating calcium phosphate layer and an alkyl chain bimodal layer located on the transition layer were prepared by microarc fluorination and nano-hydroxyapatite-induced bionic mineralization techniques.

Benefits of technology

Effectively inhibit the biocorrosion of magnesium-based materials, improve the mechanical stability and interface binding of implanted devices, promote osseous binding and osteogenesis, and have excellent in vivo corrosion resistance and biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564931A_ABST
    Figure CN119564931A_ABST
Patent Text Reader

Abstract

According to the multilayer hybrid coating imitating the biological cell membrane structure and the preparation method of the multilayer hybrid coating imitating the biological cell membrane structure, hydrophobicity and biological activity are organically combined in the same coating by imitating the biological cell membrane structure for the first time, and the problem that a traditional organic hydrophobic coating is poor in tissue integration and osteogenesis performance is solved. And the transition layer with MgF2 as the main component is adopted to enhance the interface bonding force between the coating and the magnesium substrate, so that the mechanical stability of the coating and the reliability in long-term use are improved. A rat subcutaneous implantation experiment proves that the coating has excellent in-vivo corrosion resistance and biocompatibility, in-vivo corrosion of the magnesium-based material can be effectively inhibited, and the coating has good tissue binding potential. In conclusion, according to the multilayer hybrid coating with the biomimetic cell membrane structure and the preparation method of the multilayer hybrid coating, the biological corrosion of magnesium can be inhibited, the potential of promoting osseointegration and formation can be achieved, and the multilayer hybrid coating has wide application prospects especially in the fields of repairing of the orthopedics department and the stomatology department and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of medical implantable medical devices such as oral, orthopedic, and cardiac stents, and in particular relates to a multilayer hybrid coating imitating a biological cell membrane structure and a preparation method thereof. Background Art

[0002] Magnesium metal and its alloy materials have density and mechanical properties that are extremely similar to those of human bones, good biocompatibility and in vivo degradability, and are widely considered to be the next generation of breakthrough implant materials, with broad application prospects in medical devices such as dentistry, orthopedics and heart stents. However, due to its low reduction potential and active nature, magnesium metal corrodes too quickly and uncontrollably after implantation in the human body, causing problems such as high pH around the implant, hydrogen production, and loss of mechanical properties, affecting the tissue compatibility of magnesium metal and the effect of bone tissue repair, and even bringing about the safety hazard of tissue necrosis, which greatly limits its further clinical application transformation.

[0003] Up to now, surface coating technology is still considered to be a direct and effective means to delay the in vivo corrosion of magnesium-based metals. Moreover, when bioactive materials are selected as coatings, while solving the corrosion problem, magnesium-based materials will also be given certain biological functions to achieve clinical multifunctionality. CN102286767A discloses a composite coating on the surface of a magnesium alloy biological implant material and a preparation method thereof, which uses micro-arc oxidation technology to form an oxide porous film in situ on the magnesium atoms on the surface of the magnesium alloy substrate as a transition layer, and then a DLC film layer is provided on the transition layer to reduce electrochemical corrosion. However, the above structure does not isolate the contact between the magnesium-based metal and the corrosive medium, so it will continue to be affected by in vivo corrosion. Therefore, using a hydrophobic modified material (such as a polymer, a surfactant or a micro / nanostructured material) as a physical barrier to isolate the contact between the magnesium-based metal and the corrosive medium is a more effective anti-corrosion means.

[0004] However, hydrophobicity often inhibits the biological activities of cells such as adhesion, proliferation and differentiation on the surface of implanted devices, thereby affecting the subsequent tissue integration and bone regeneration effects. Directly incorporating bioactive substances into the skeleton of hydrophobic materials without structural design may destroy the compact structure of the hydrophobic coating and reduce its anti-corrosion effect. In addition, the poor interface matching between the hydrophobic coating and the magnesium-based metal substrate leads to the shedding and long-term instability of the coating. Therefore, it is urgent to develop a next-generation coating technology that can effectively combine good corrosion resistance, biocompatibility and excellent interface bonding to obtain high-performance magnesium-based metal implants. Summary of the invention

[0005] In order to overcome the technical problems existing in the above-mentioned prior art, the present invention proposes a multilayer hybrid coating imitating a biological cell membrane structure and a preparation method thereof.

[0006] Specifically, the present invention proposes a multilayer hybrid coating that mimics a biological cell membrane structure, including a transition layer formed on the surface of a magnesium-based metal, and a biological cell membrane structure coating located on the transition layer, wherein the bionic cell membrane structure coating is an alternating calcium phosphate layer and an alkyl chain bilayer, wherein the main component of the calcium phosphate layer is octacalcium phosphate.

[0007] Furthermore, the transition layer is a porous coral-like structure, the main component of which is MgF2.

[0008] Furthermore, the biological cell membrane-mimicking coating presents a flaky nanostructure.

[0009] Furthermore, the biological cell membrane-mimicking structure coating is hydrophobic.

[0010] Furthermore, the bio-mimicking cell membrane structure coating and the transition layer are interlocking structures.

[0011] Correspondingly, the present invention also proposes a method for preparing a multilayer hybrid coating of a bionic cell membrane structure, and the specific process is as follows:

[0012] (1) Preparation of transition layer: A transition layer (hereinafter referred to as MAF layer) is prepared on the magnesium surface using a micro-arc fluorination (MAF) process;

[0013] (2) Preparation of fluoroapatite coating (hereinafter referred to as FAP layer): The fluoroapatite coating is formed by biomineralization induced by nanohydroxyapatite NanoHAP;

[0014] (3) Preparation of coatings with biomimetic cell membrane structures: The fluoroapatite coating is reacted with a dodecyl phosphate surfactant to transform the fluoroapatite coating into a flaky biomimetic cell membrane structure coating.

[0015] The method for preparing the transition layer specifically includes:

[0016] 1) Use laser to cut magnesium sheets into disc-shaped samples;

[0017] 2) Use sandpaper to polish gradually in ethanol to obtain a smooth surface;

[0018] 3) During the micro-arc fluorination MAF process, the magnesium sample was used as the anode and the graphite rod was used as the cathode, immersed in a PTFE container containing 46wt.% hydrogen fluoride, and a constant voltage of 185~190V and a current of 0.145~0.155A were applied through the DC power supply constant voltage mode. The current was 0.045A, and the reaction continued until the current dropped to less than 0.01A, indicating that the reaction was completed;

[0019] 4) The treated samples were rinsed three times with distilled water and air-dried at room temperature.

[0020] The preparation method of the fluoroapatite coating specifically includes:

[0021] 1) The samples after transition layer treatment were immersed in 2wt.% NanoHAP seed suspension and left for 30 min;

[0022] 2) Air dry at room temperature for 2 hours;

[0023] 3) The samples including NanoHAP seeds were immersed in the mineralization solution and incubated at 37 °C for 3 h to induce the remineralization of NanoHAP seeds to form a fluorapatite coating;

[0024] 4) Air dry at room temperature.

[0025] The method for preparing the coating with a biomimetic cell membrane structure specifically includes:

[0026] 1) After the second air drying, the sample was immersed in a 2 wt.% dodecyl phosphate surfactant solution (pH value: 10 ± 0.5, adjusted with 20% NaOH) and allowed to stand for 2 h;

[0027] 2) The obtained biomimetic cell membrane structure coating was thoroughly rinsed with deionized water and air-dried at room temperature.

[0028] Compared with the prior art, the present invention has at least the following beneficial effects:

[0029] The present invention proposes a multilayer hybrid coating that mimics the structure of biological cell membranes for the first time. By imitating the structure of biological cell membranes for the first time, hydrophobicity and biological activity are organically combined in the same coating, solving the problem that traditional hydrophobic coatings are difficult to promote tissue integration and bone formation. In addition, a transition layer whose main component is MgF2 is used to enhance the interfacial bonding between the coating and the magnesium substrate, thereby improving the mechanical stability of the coating and the reliability in long-term use. In addition, through the verification of subcutaneous implantation experiments on rats, it is proved that the coating has excellent body corrosion resistance and biocompatibility, can effectively inhibit the corrosion of magnesium-based materials, and has good tissue binding potential. In summary, the multilayer hybrid coating that mimics the structure of biological cell membranes proposed by the present invention can not only inhibit the biological corrosion of magnesium, but also has the potential to promote bone integration and bone formation, especially in the fields of bone repair in orthopedics and stomatology, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the functionality, internal structure and preparation process of the multilayer hybrid coating imitating the biological cell membrane structure on magnesium metal in the present invention. Figure 1Middle: a is a schematic diagram of the rapid corrosion of pure magnesium; b is a schematic diagram of the dual functions of the OCP-SH coating; c is a schematic diagram of the multilayer hybrid structure of the OCP-SH coating; d is a schematic diagram of the preparation process of the OCP-SH coating.

[0031] Figure 2 It is the characterization of the magnesium metal coating in the present invention. Figure 2 Middle: SEM images in ac show the surface morphologies of MAF, FAP and OCP-SH coatings, respectively; d is the small-angle XRD spectrum of the magnesium metal coating; e is the FTIR spectrum of the magnesium metal coating; f is the water contact angle test result of the magnesium metal coating.

[0032] Figure 3 These are the test results of the mechanical properties and interface bonding strength of the coating in the present invention. Figure 3 Middle: SEM images in ac show the porous MAF layer (a), and the interlocking interfaces between the FAP layer and the MAF layer (b) and between the OCP-SH layer and the MAF layer (c), respectively. The interfaces are marked by yellow dotted lines; df are the optical surface image of the coating scratch test (d), the displacement-scratch depth curve (e), and the critical force of interface rupture (f), respectively.

[0033] Figure 4 This is the experimental result of the corrosion resistance of the coating in the present invention. Figure 4 Middle: a and b are the results of electrochemical tests conducted in simulated body fluid (SBF), including the EIS spectra (Figure a) and potentiodynamic polarization curves (PDP) (Figure b) of pure magnesium and samples coated with MAF, FAP / MAF and OCP-SH / MAF coatings; c is the result of the hydrogen release test in SBF for 912 hours, and the inset shows a digital photo of the sample with a diameter of 8 mm after the test; d is the magnesium ion release data of a 28-day immersion test in α-MEM containing 10wt.% fetal bovine serum albumin (FBS).

[0034] Figure 5 These are the experimental results of the in vitro cell compatibility and bone-promoting ability of the coating of the present invention. Figure 5Middle: a is a confocal fluorescence image of MC3T3-E1 cells and human gingival fibroblasts (HGFs) on pure magnesium and coated magnesium, showing the cell adhesion morphology after 4 hours, 24 hours and 72 hours of culture, respectively. The cell nucleus is stained blue, actin filaments are stained red, and adhesion focal protein (vinculin) is stained green. The scale bar of the fluorescence image is 20μm; b and c show the biocompatibility of HGFs and MC3T3-E1 cells evaluated by CCK-8 experiment, respectively, and the cell proliferation after 24 hours, 48 ​​hours and 72 hours of culture was tested; d shows the alkaline phosphatase (ALP) activity of human bone marrow mesenchymal stem cells (hBMSCs) under osteogenic induction conditions after 7 days of culture on different substrates.

[0035] Figure 6 It is a comparison chart of the in vivo corrosion resistance and biocompatibility of the coating of the present invention. Figure 6 Middle: ad are the cross-sectional morphology and corresponding element distribution of magnesium substrate (Figure a), MAF-coated magnesium (Figure b), FAP-coated magnesium (Figure c) and OCP-SH / MAF-coated magnesium (Figure d) after 4 weeks of implantation. Figure a is at a 30μm scale, and Figures bd are at a 9μm scale; Figure e is an optical micrograph of H&E staining of the subcutaneous tissue around the implant after 1 and 4 weeks of implantation at a scale of 100μm, where "*" indicates the insert and the blue stained area is the inflammatory cell. DETAILED DESCRIPTION

[0036] In the following, in conjunction with the accompanying drawings in the examples of the present invention, a multilayer hybrid coating imitating a biological cell membrane structure and a preparation method thereof are further described. The following examples are only used to illustrate the present invention and are not intended to limit the present invention.

[0037] like Figure 1 As shown in a, magnesium-based implants have the problems of rapid biocorrosion and insufficient bone integration. Based on such technical problems, the present invention finds that in nature, the structure of biological cell membranes cleverly combines the hydrophobic isolation region with the hydrophilic biological active region, and can further closely combine with other cells or substrates through special connection structures such as glycoprotein anchor connection structures.

[0038] The layered calcium phosphate material, octacalcium phosphate (OCP), has the advantages of both calcium phosphate materials and layered materials. First, OCP has good biocompatibility, strong bone tissue affinity, and osteogenic bioactivity. Secondly, the layered structure of OCP consists of apatite layers and hydration layers. The hydration layer can introduce different guest molecules through substitution, including organic molecules such as cations, dicarboxylic acids, aminotriols and silicon. Based on this structural feature, hydrophobic organic materials can be introduced into inorganic OCP bioactive materials to construct organic / inorganic hybrid materials.

[0039] Therefore, in order to highly mimic the structure of biological cell membranes, the present invention selects a phospholipid-like dodecyl phosphate (MDP) surfactant, specifically sodium monododecyl phosphate, as a guest molecule, which is inserted into the hydration layer of the OCP main structure. In this way, a hybrid coating of alternating bioactive OCP layers and hydrophobic alkyl chain bilayers is formed, thereby effectively combining hydrophobicity with bioactivity. At the same time, the coating can inhibit magnesium biocorrosion and promote osteogenesis, and has great potential in the application of magnesium-based implants.

[0040] Specifically, the present invention proposes a multilayer hybrid coating that mimics a biological cell membrane structure, which includes a transition layer formed on the surface of a magnesium-based metal by a micro-arc fluorination MAF process, and a biological cell membrane structure coating (hereinafter referred to as OCP-SH coating) located on the transition layer. The biological cell membrane structure coating is an alternating calcium phosphate layer and an alkyl chain bilayer. Among them, the main component of the calcium phosphate layer is octacalcium phosphate. The main component means that it occupies a large proportion, such as the content of the component in the present invention is greater than 50%, and it can also be preferably 60%, 70%, 80% or more than 90%, and it is the core of the calcium phosphate layer, which determines the basic physical, chemical and biological properties of the calcium phosphate layer. The coating combines the alternatingly arranged biologically active OCP layer and the hydrophobic alkyl chain bilayer, which not only enhances the corrosion resistance, but also promotes the biological activity (such as Figure 1 b and c). The hydrophobic phospholipid-like alkyl chain bilayer structure in the coating can effectively prevent the penetration of corrosive biological fluids, while the surface bioactive OCP layer is conducive to the integration of cells. In order to realize the coating, the present invention adopts a step-by-step in situ growth method (such as Figure 1 (d)

[0041] The material characterization of the multilayer hybrid coating proposed by the present invention is as follows:

[0042] Scanning electron microscopy (SEM) was used to observe the coating morphology, which showed that the MAF layer had a highly porous coral-like structure (thickness was about 2-7 μm), while the OCP-SH layer exhibited a flaky nanostructure (coating thickness was about 1 μm) (e.g. Figure 2 ac). The OCP-SH coating and the MAF layer have an interlocking structure. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) show that the OCP-SH coating has a highly ordered layered structure (e.g. Figure 2 In addition, the water contact angle test of the coating showed that the OCP-SH coating had significant hydrophobicity (contact angle 148.5°) (see Figure 5). Figure 2 f). These results demonstrate the successful preparation of OCP-SH coatings.

[0043] The present invention also proposes a method for preparing a multilayer hybrid coating that mimics a biological cell membrane structure:

[0044] (1) Preparation of MAF layer: A transition layer (hereinafter referred to as MAF layer) is prepared on the magnesium surface using the micro-arc fluorination (MAF) process. This layer provides initial corrosion protection and supports the deposition of subsequent coatings and enhances interface bonding through a porous structure, effectively mechanically intercalating the OCP-SH coating with the magnesium substrate, ultimately ensuring the in-situ formation of the OCP-SH coating and improving the adhesion and interface bonding stability of the coating.

[0045] (2) Preparation of fluorapatite coating (FAP layer): Fluorapatite coating is formed by biomimetic mineralization induced by nanohydroxyapatite (NanoHAP).

[0046] (3) Preparation of OCP-SH coating: The FAP layer was reacted with dodecyl phosphate (MDP) surfactant for 2 hours to transform it into a flaky OCP-SH coating. The MDP surfactant was intercalated into the OCP main body by an in situ chemical reaction between the FAP layer and the MDP surfactant, forming an alternating bilayer of bioactive calcium phosphate layers (OCP layers) and hydrophobic alkyl chains, thereby achieving an organic combination of hydrophobicity and bioactivity to form a coating with dual functions.

[0047] The preparation method also includes the following steps of preparing the nano-HAP seed suspension and the mineralization solution:

[0048] 1) Preparation of NanoHAP Seed Suspension: NanoHAP seed suspension was prepared by mixing 2 wt.% NanoHAP particles with 1 wt.% gelatin binder in ultrapure water and ultrasonicating for 40 min. This suspension served as a precursor for the subsequent NanoHAP seed adsorption process.

[0049] 2) Preparation of mineralization solution: The mineralization solution (artificial saliva) was prepared by adding 5 ppm fluoride ions to NaF reagent and was composed of 1 mM CaCl2·2H2O, 4 mM KH2PO4, 20 mM HEPES, 16 mM KCl, 4.5 mM NH4Cl and 0.2 mM MgCl2·6H2O, and the pH value was adjusted to 7.0.

[0050] The preparation method of the MAF layer specifically includes:

[0051] 1) Cutting the magnesium sheet into a disc by laser, wherein the magnesium sheet is a commercial magnesium sheet, specifically, the commercial magnesium sheet produced by Dongguan Feitai Metal Products Co., Ltd., and the size of the disc can be Ø16×1.5mm, Ø8×0.5mm, or other sizes. The present invention takes a disc sample with a diameter of 16×1.5mm as an example;

[0052] 2) Use 1000# and 2000# SiC sandpaper to polish gradually in ethanol to obtain a smooth surface;

[0053] 3) During the micro-arc fluorination (MAF) process, the magnesium sample was used as the anode and the graphite rod was used as the cathode, immersed in a PTFE container containing 46wt.% hydrogen fluoride. Through the DC power supply constant voltage mode, a constant voltage of 185~190V was applied, and the current was 0.145~0.155A. The reaction continued until the current dropped to less than 0.01A, indicating that the reaction was complete.

[0054] 4) The treated samples were rinsed three times with distilled water and air-dried at room temperature.

[0055] The preparation method of the FAP layer specifically includes:

[0056] 1) The MAF layer-treated samples were immersed in a 2 wt.% nano-HAP seed suspension and left for 30 min to allow the seed crystals to adsorb onto the porous surface;

[0057] 2) Air dry at room temperature;

[0058] 3) The samples including NanoHAP seeds were immersed in the mineralization solution and incubated at 37 °C for 3 h to induce the remineralization of NanoHAP seeds to form a fluorapatite (FAP) coating;

[0059] 4) Air dry at room temperature.

[0060] The preparation method of the OCP-SH coating specifically includes:

[0061] 1) After the second air drying, the sample was immersed in a 2 wt.% MDP solution (pH: 10 ± 0.5, adjusted with 20% NaOH) and left for 2 h to promote the in situ reaction between the FAP layer and the MDP surfactant;

[0062] 2) The obtained OCP-SH coating samples were thoroughly rinsed with deionized water and air-dried at room temperature.

[0063] The experimental results of the multilayer hybrid coating imitating the biological cell membrane structure proposed by the present invention are analyzed as follows:

[0064] 1. Mechanical properties analysis is as follows:

[0065] The mechanical properties of the coating are crucial to its practicality. The present invention uses a nano scratch tester to test the adhesion strength of the coating, using a diamond indenter, gradually increasing the lateral force to a maximum of 5N, and performing a lateral movement of 30μm.

[0066] To enhance the interfacial adhesion of the OCP-SH coating, the MAF layer provides a porous structure that enhances the physical intercalation effect (e.g. Figure 3 Nanoindentation scratch test shows that its adhesion strength is significantly improved, reaching 4.57±0.02N / cm (such as Figure 3 The corrosion resistance of the coating proposed by the present invention is analyzed as follows:

[0067] The present invention uses an electrochemical workstation to test corrosion performance. A classic three-electrode cell is used, the working electrode is a sample with an exposed area of ​​1 cm², the reference electrode is a saturated potassium chloride electrode, and the auxiliary electrode is a platinum electrode. At room temperature, the sample is immersed in 300 ml of simulated body fluid (SBF) for 30 minutes to reach a stable open circuit potential. Electrochemical impedance spectroscopy (EIS) tests are performed with a frequency range of 0.1 Hz to 10 5 Hz, with an amplitude of 20 mV; and a polarization curve test (PDP) was performed with a scan range of -250 mV to +250 mV (relative to the open circuit potential) and a scan rate of 0.225 mV / s.

[0068] The present invention uses hydrogen release to evaluate the long-term corrosion resistance of the coating. Coated and uncoated magnesium samples (n=3) are immersed in SBF (20ml / cm²), and a funnel and burette system are used to capture and quantify the hydrogen release to directly evaluate the effect of the coating in inhibiting hydrogen release during corrosion.

[0069] The electrochemical impedance spectroscopy (EIS) test and the potentiodynamic polarization curve (PDP) test showed that the OCP-SH coating showed excellent anti-corrosion performance in simulated body fluid (SBF), and its impedance modulus was 1.51×10 6 Ω·cm², which is 13 times that of MAF and FAP / MAF coatings (e.g. Figure 4 The 912-hour hydrogen release experiment showed that the hydrogen release of the OCP-SH coating was reduced by 87%, indicating its excellent long-term corrosion resistance (e.g. Figure 4 The 28-day magnesium ion release experiment further verified the stability of the coating (e.g. Figure 4 (d)

[0070] 2. The in vitro cell compatibility and bone-promoting ability experiments of the coating proposed by the present invention are as follows:

[0071] (1) In vitro magnesium ion leaching test:

[0072] The immersion medium was α-MEM containing glucose, amino acids and 10wt.% fetal bovine serum (FBS) to simulate complex biological fluids. In the in vitro immersion method, coated and uncoated magnesium samples (n=3, Ø16×1.5mm) were placed in a 24-well plate, 2ml of immersion medium was added, and it was replaced every 24 hours. The supernatant of three parallel samples was analyzed by inductively coupled plasma spectrometry to quantify the amount of magnesium ion leaching at different time points.

[0073] (2) In vitro cell proliferation assay

[0074] After the samples were sterilized under ultraviolet irradiation for 2 hours, the four groups of samples, Mg, MAF, FAP / MAF, and OCP-SH / MAF, were immersed in α-MEM overnight. Then, mouse calvarial preosteoblasts (MC3T3-E1) and human gingival fibroblasts (HGFs) were cultured at 3×10 4 The density of cells / sample was seeded onto the material surface and cultured in α-MEM and DMEM containing 10% FBS and 1% penicillin-streptomycin, respectively, and incubated at 37°C in an atmosphere of 5% CO2. Cell proliferation was measured at intervals of 24 h after seeding using the CCK-8 method.

[0075] (3) In vitro cell adhesion observation

[0076] To observe the adhesion morphology of cells at 4 hours, 24 hours, and 72 hours, the samples were first fixed with 4% paraformaldehyde. Subsequently, the cytoskeletal protein F-actin was stained red with fluorescein-labeled phalloidin-rhodamine, and the nucleus was stained blue with DAPI. At 24 hours, the adhesion plaque protein was further stained green with fibronectin / FN1. Finally, a confocal laser scanning microscope was used to capture three-dimensional images.

[0077] (4) In vitro cell differentiation experiment

[0078] Human bone marrow mesenchymal stem cells were expressed at 1×10 5 After two days of culture, the osteogenic differentiation of hBMSCs was promoted using osteogenic induction medium, which included α-MEM medium, 10% fetal bovine serum (FBS), 1% penicillin-streptomycin, 1×10⁻ 8 mol / L dexamethasone, 2.8×10⁻ 4mol / L ascorbic acid and 6.5×10⁻³mol / L sodium β-glycerophosphate, and the medium was changed every two days. After 7 days of induction culture, alkaline phosphatase (ALP) staining and quantitative analysis were performed using the BCIP / NBT alkaline phosphatase colorimetric kit, which quantifies ALP activity by measuring the conversion of p-nitrophenyl phosphate (pNPP) to colored p-nitrophenol. The total intracellular protein concentration was determined using a protein assay kit, and the ALP activity was normalized by calculating the ratio of p-nitrophenol absorbance to total protein concentration.

[0079] The experimental results showed that OCP-SH coating exhibited excellent performance in promoting cell adhesion, proliferation and differentiation. In in vitro experiments, human gingival fibroblasts (HGFs) and mouse preosteoblasts (MC3T3-E1) showed significantly enhanced adhesion and expansion capabilities on the surface of OCP-SH coating (e.g. Figure 5 (a). Compared with uncoated magnesium, OCP-SH coating not only promoted the extension of intercellular pseudopodia, but also formed a stronger cell-cell network connection. In addition, the cell proliferation experiment showed that the proliferation ability of cells on the coated surface was significantly better than that of other groups (such as Figure 5 On human bone marrow mesenchymal stem cells (hBMSCs), the OCP-SH coating exhibited higher alkaline phosphatase (ALP) activity, indicating its potential to promote osteogenesis (e.g. Figure 5 These performance improvements can be attributed to the nanosheet structure and unique chemical properties of the coating, especially the bioactive OCP layer that mimics the bone mineral structure and the stable hydrophobic alkyl chain bilayer, which together provide a favorable microenvironment for cells.

[0080] 3. The in vivo corrosion resistance and biocompatibility experiments of the coating proposed by the present invention are as follows:

[0081] (1) Establishment of subcutaneous implantation model in rats

[0082] All animal surgical procedures in this study were approved by the Animal Ethics Committee of Peking University, with approval number PUIRB-LA2023439. Eight-week-old male Sprague-Dawley (SD) rats were used in the experiment and purchased from Beijing Weitongli Laboratory Animal Technology Co., Ltd. Before implantation, the dorsal area of ​​each rat was disinfected with iodine. Subsequently, the skin was incised bilaterally along the midline of the back to create subcutaneous pouches, with three pouches set on each side of the spine as the central axis. Samples from the four groups, including Mg, MAF-Mg, FAP / MAF-Mg, and OCP-SH / MAF (sample size was Ø8×0.5 mm), were randomly inserted into each pouch. Antibiotics were used to prevent infection in the animals after surgery to ensure that the animals remained healthy throughout the study.

[0083] (2) Internal corrosion analysis

[0084] Four weeks after implantation, the animals were euthanized and three samples were removed from each group. The samples were fixed in 10% neutral formalin for 48 h to maintain their structural integrity. The surface tissue was then digested with 0.25% trypsin-EDTA to expose the implant. The removed samples were embedded in epoxy resin and sequentially polished with 1000#, 2000#, and 5000# silicon carbide (SiC) sandpaper, and then polished with silk cloth in an ethanol environment. In order to enhance the surface conductivity, a carbon layer was deposited on the exposed cross section using a high vacuum ion sputtering instrument. The morphology and elemental composition of the corrosion layer were analyzed by scanning electron microscopy (SEM) and energy dispersive spectroscopy (SEM-EDS).

[0085] (3) In vivo biocompatibility analysis

[0086] To assess tissue compatibility, animals were euthanized at 1 and 4 weeks after implantation. The implants and surrounding tissues were carefully excised and fixed in 10% neutral formalin for 48 h. The tissues were then washed, dehydrated in 70% ethanol, and embedded in paraffin for histological analysis. Paraffin-embedded samples were cut into 5-μm-thick sections and stained with hematoxylin-eosin (H&E) to assess cellular infiltration and fibrous pocket formation. Panoramic images of the stained sections were captured using a high-resolution digital scanner to document and analyze tissue reactions.

[0087] The experimental results showed that after the samples were implanted subcutaneously in SD rats for 4 weeks, the OCP-SH coating showed significant in vivo corrosion resistance, with a corrosion depth of only 1.1 μm, which was significantly lower than that of MAF and FAP coatings (e.g. Figure 6 Histological analysis showed that all samples triggered inflammatory responses at the initial stage of implantation, but the thickness of the fibrous capsule of the OCP-SH coating was only 65.2 μm, significantly lower than that of the other coating groups and uncoated magnesium, and maintained the lowest inflammatory response after 4 weeks (e.g. Figure 6 These results indicate that the OCP-SH coating has excellent in vivo biocompatibility and long-term anti-corrosion performance, providing reliable support for the clinical application of magnesium-based implants.

[0088] The above embodiments describe the present invention in detail, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A multilayer hybrid coating that mimics a biological cell membrane structure, comprising a transition layer formed on a magnesium-based metal surface, and a biological cell membrane structure coating located on the transition layer, wherein the biological cell membrane structure coating is an alternating arrangement of calcium phosphate layers and alkyl chain bilayers, wherein the main component of the calcium phosphate layer is octacalcium phosphate.

2. The multilayer hybrid coating imitating a biological cell membrane structure according to claim 1, characterized in that: The transition layer is a porous coral-like structure, and its main component is MgF2.

3. The multilayer hybrid coating imitating a biological cell membrane structure according to claim 1, characterized in that: The bio-mimicking cell membrane structure coating presents a flaky nanostructure.

4. The multilayer hybrid coating imitating a biological cell membrane structure according to claim 1, characterized in that: The bio-mimicking cell membrane structure coating is hydrophobic.

5. The multilayer hybrid coating imitating a biological cell membrane structure according to claim 1, characterized in that: The bio-mimicking cell membrane structure coating and the transition layer are interlocking structures.

6. A method for preparing a multilayer hybrid coating having a biological cell membrane structure as claimed in any one of claims 1 to 5, wherein the specific process is as follows: (1) Preparation of transition layer: The transition layer is prepared on the magnesium surface using the micro-arc fluorination (MAF) process; (2) Preparation of fluoroapatite coating: The fluoroapatite coating is formed by biomineralization induced by nanohydroxyapatite NanoHAP; (3) Preparation of coatings with biomimetic cell membrane structures: The fluoroapatite coating is reacted with a dodecyl phosphate surfactant to transform the fluoroapatite coating into a flaky biomimetic cell membrane structure coating.

7. The method for preparing a multilayer hybrid coating imitating a biological cell membrane structure according to claim 6, characterized in that: The preparation method of the transition layer specifically includes: 1) Use laser to cut magnesium sheets into disc-shaped samples; 2) Use sandpaper to polish gradually to obtain a smooth surface; 3) During the micro-arc fluorination MAF process, the magnesium sample is used as the anode and the graphite rod is used as the cathode. They are immersed in a PTFE container containing 46wt.% hydrogen fluoride. A constant voltage of 185-190V is applied through the DC power supply constant voltage mode. The reaction continues until the current drops to less than 0.01A, indicating that the reaction is complete; 4) The treated samples were rinsed three times with distilled water and air-dried at room temperature.

8. The method for preparing a multilayer hybrid coating imitating a biological cell membrane structure according to claim 6, characterized in that: The preparation method of the fluoroapatite coating specifically includes: 1) The sample after transition layer treatment was immersed in 2wt.% NanoHAP seed suspension and left for 30 min; 2) Air dry at room temperature; 3) The sample including the nanohydroxyapatite NanoHAP seeds was immersed in a mineralization solution and incubated at 37 °C for 3 h to induce the remineralization of the nanohydroxyapatite NanoHAP seeds to form a fluoroapatite coating; 4) Air dry at room temperature.

9. The method for preparing a multilayer hybrid coating imitating a biological cell membrane structure according to claim 6, characterized in that: The preparation method of the coating imitating biological cell membrane structure specifically includes: 1) After the second air drying, the sample was immersed in a 2 wt.% dodecyl phosphate surfactant solution and left to stand for 2 hours; 2) The obtained biomimetic cell membrane structure coating was thoroughly rinsed with deionized water and air-dried at room temperature.

10. The method for preparing the multilayer hybrid coating imitating the biological cell membrane structure according to claim 9, characterized in that: The pH of the dodecyl phosphate surfactant solution was 10 ± 0.5, adjusted using 20% ​​NaOH.

Citation Information

Patent Citations

  • Absorbable metal intramedullary nail and preparation method thereof

    CN101690676A

  • Surface coating for magnesium alloy intra-bony fixing products and preparation method thereof

    CN103505763A

  • Hydroxyapatite coating with biological activity and hierarchical structure on surface of degradable magnesium-based endosteal implant and preparation method

    CN111973812A

  • Medical magnesium alloy surface magnesium fluoride / hydroxyapatite composite coating and preparation method thereof

    CN118773610A

  • Film mirror for solar power generation, method for manufacturing film mirror for solar power generation, and reflecting device for solar power generation

    JP2013245849A